Social Responsibility Initiatives Supporting Ngos in Oradea Municipality - C. Bacter; C. Marc (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
The paper highlights the main needs and challenges faced by non-governmental organizations that provide social services in the municipality of Oradea and analyzes how they are supported by corporate social responsibility actions. The data obtained show that financial needs prevail and generate difficulties in the functioning of organizations. The support of companies is generally occasional and consists mainly of sponsorships and employee volunteering.